Cystic Fibrosis and Reproductive Outcomes: The Latest Insights into Fertility and Pregnancy - Małagocka, Weronika; Zagórski, Karol; Kozik, Mateusz; Skalska-Dziobek, Nina; Chybowska, Karolina; Naruszewicz, Maria; Cetnarowski, Przemysław (Quality in Sport, 2025)
Introduction and purpose: Due to improvement in treatment of people with cystic fibrosis (CF), the number of adult patients increases. CF patients are living longer, with better quality of life and a growing number of them are considering parenthood. Most people with CF are suffering because of reduced fertility, however the number of pregnant CF patients rises. The aim of this paper was to summarize the date available in the literature and recent reports about the fertility, pregnancy and treatment of pregnant CF patients. Material and methods: The literature was reviewed in PubMed database, GoogleScholar and in European Cystic Fibrosis Society database with the use of keywords. State of knowledge:78% of women with CF declare that they want to have a child in the future. Reduced fertility may be overcome with assisted reproduction technologies, which also gives an opportunity to do preimplantation genetic tests. CFTR modulators therapy during the pregnancy was described in a small number of studies, but the current experts statement declares that those drugs are probably safe for the infant, and discontinuing this therapy is connected with an increased risk of pulmonary exacerbation in mothers. Summary: Women with CF nowadays have an opportunity to become parents. Despite fertility lower than in the general population, they are able to become pregnant. The decision about the conception should be planned before and consulted with the CF team. Planning the pregnancy gives time to prepare the mother, optimize her nutrition status and make sure medications she takes are safe for the fetus. Data about the use of CFTR modulators during pregnancy and breastfeeding are limited. In the future the MAYFLOWER study may determine the impact of CFTR modulators on pregnancy and breastfeeding.